The Complications of Literary Consciousness in A Marčėnas’ Poetry - Klimaitė, Eglė (Respectus Philologicus, 1999)
The purpose of this interpretation study is to disclose the poet’s unique lyrical nature as well as some symptoms of his second-rate literariness judging by his fluent language versus instances of imitation that do not correspond to the classical image of the author used by many a critic.